2010
DOI: 10.4161/cbt.9.11.11873
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the histone deacetylase inhibitor romidepsin (FK228) are enhanced by aspirin (ASA) in COX-1 positive ovarian cancer cells through augmentation of p21

Abstract: Histone deacetylase (HDAC) inhibitors have shown preclinical efficacy in solid tumors, including ovarian cancers. Our group has published that the HDAC inhibitor, romidepsin (FK228) suppresses ovarian cancer cell growth at nanomolar concentrations in vitro. HDAC inhibitors appear to be even more effective when used in combination with other anti-tumor agents. However, it remains unclear which anti-tumor agents are best suited for combination therapy. A recent report suggested that aspirin (acetylsalicylic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…Our data demonstrated that the combination treatment caused a large relative decrease in the expression of COX-1 and PGE2 as compared to in the control or single-agent treatment.Wheras the expression levels of COX-2 was not altered in response to exemestane, aspirin alone, or the combination. Some preclinical studies have also shown that COX-1 selective inhibition exhibited significant inhibitory effects in bladder cancer cells in vitro (Mohseni et al, 2004), ovarian cancer cell lines (Daikoku et al, 2005;Daikoku et al, 2006;Son et al, 2010) and human breast cancer (Connolly et al, 2002;Kundu and Fulton 2002;Ristimaki et al, 2002;McFadden et al, 2006;Howe 2007). These data suggest that COX-1 may play an important role of the anticancer activity in our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data demonstrated that the combination treatment caused a large relative decrease in the expression of COX-1 and PGE2 as compared to in the control or single-agent treatment.Wheras the expression levels of COX-2 was not altered in response to exemestane, aspirin alone, or the combination. Some preclinical studies have also shown that COX-1 selective inhibition exhibited significant inhibitory effects in bladder cancer cells in vitro (Mohseni et al, 2004), ovarian cancer cell lines (Daikoku et al, 2005;Daikoku et al, 2006;Son et al, 2010) and human breast cancer (Connolly et al, 2002;Kundu and Fulton 2002;Ristimaki et al, 2002;McFadden et al, 2006;Howe 2007). These data suggest that COX-1 may play an important role of the anticancer activity in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study,we investigated that aspirin exhibited remarkably anti-proliferative effects and dose dependent growth inhibition on MCF-7 human breast cancer cells. Some preclinical studies have shown that aspirin synergistically enhanced the anti-tumor effect of chemotherapy in ovarian cancer and colon cancer (Kanthamneni et al, 2010;Son et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others have shown that nanomolar concentrations of FK228 effectively reduce cell viability in ovarian cancer cells [5, 11, 21, 22]. Here, we evaluated the anti-proliferative and cytotoxic effects of FK228 (1– 10 nM), cisplatin (0.5–5 μM) and the combination by conducting SRB cellular assays 72 h after drug exposure (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
“…HDACI have shown preclinical efficacy in solid tumors, including ovarian cancers. A recent study reported that the combined treatment of the HDACI and COXs inhibitor showed enhanced anti tumor effects in ovarian cancer cells [29]. …”
Section: Discussionmentioning
confidence: 99%